DAMPAK EKONOMI DIGITAL DALAM MENINGKATKAN EFISIENSI LAYANAN POS MELALUI APLIKASI POS AJA DI KANTOR POS CABANG NGAWI - Melati, Septiyan Tri; Anifah, Siti (Commodity : Jurnal Perbankan dan Keuangan Islam, 2025)
ABSTRACT The development of digital technology has brought significant changes to various sectors of the economy, including courier services. In the context of the digital economy, the adoption of technology enhances operational efficiency, reduces costs, and improves service quality. PT Pos Indonesia has responded by launching the Pos Aja application, which facilitates users in accessing parcel delivery services online. This application allows users to order, track packages, obtain rate information, and make payments easily. The main benefits of the Pos Aja application include ease of access, reduced waiting times, and cost efficiency. This research explores the efficiency of the Pos Aja application compared to conventional methods, addressing questions regarding productivity, time flexibility, and challenges in digitalization. The novelty of this research lies in its focus on the Ngawi Post Office branch, which faces unique digital infrastructure challenges. This study provides new insights into the implementation of the Pos Aja application and offers recommendations for PT Pos Indonesia to enhance the effectiveness of digitalization. It is also expected to provide guidance for policymakers on the importance of digital infrastructure in the transformation of public services. Keywords: Digital Economy, Pos Aja Application, Digital Services, Service Efficiency